“Grave: Metamorfozy Na Wiolonczelę I Fortepian” By Witold Lutoslavski: The Role Of Derivation In The Embodiment Of The Idea Of Metamorphosis - Korchev, Oleksandr (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of research. The relevance of the article lies in the empirical study of new phenomena in the field of composition, understanding the essence of the concept of metamorphosis on the basis of its practical detection in the works of W. Lutoslavski, for its further characterization in modern terminological dictionary of theoretical musicology. The purpose of the study. The aim of this article is to consider the embodiment of the phenomenon of metamorphosis through the prism of derivation in the work “Grave: Metamorphosis for Cello and Piano” (1981) by W. Lutoslavski. The objectives of the presented work are analytical consideration of the compositional features of the structural organization of “Grave”, the definition of leading methods of working with thematic material, characterization of the basic principles of formation of the musical text of this work. Methods. The article uses system, comparative, genre research methods, as well as methods for a holistic and structural analysis of a musical work. The results and conclusions. The concept of metamorphosis in the works of Polish composer W. Lutoslawski is considered, on the example of his work for cello and piano “Grave”. By comparing the above opus with W. Lutoslavski’s Muzyka żałobna (1958), the place of the idea of “transformation” in the creative work of the outstanding artist was determined. With the help of holistic analysis, the main means of working with thematic material were identified, which is the basis for the embodiment of the phenomenon of metamorphosis in the thematic material of “Grave”. The relationship between the composer’s idea of metamorphosis and the principle of derivation by M. Aranovsky is illustrated on the example of analytical consideration of “Grave”. The paper presents the embodiment of this concept of transformation through the prism of derivation, by analytical consideration of the functioning of borrowed material in the formation of a new compositional whole, its impact on the characteristics of the structural organization of the work.